The protection of children and adolescents from violence - Ribeiro, Juliane Portella; Silva, Mara Regina Santos da; Cezar-Vaz, Marta Regina; Silva, Priscila Arruda da; Silva, Bárbara Tarouco da (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> In this paper, public protection policies for children and adolescents are analyzed from a health perspective. Interfaces between them, public protection and health policies are presented. Then, the policies are discussed from a conceptual and philosophical viewpoint, also considering the limitations and potentials observed. Findings showed that the strong impact of violence on child and adolescent morbidity and mortality in the Brazilian population has lead to the restructuring of the victim protection network, demanding problem-solving care. Nurses’ inclusion in the child and adolescent protection network is fundamental, as these professionals are in a strategic position to identify risks and possible victims. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->